The Imperialist Epistemological Vision (American Journal of Islam and Society, 1994)
There is a view that imperialism, as a historical practice, constitutesa deviation from western civilization and its conception of the universe,and that the adoption of the imperialist solution, which involves exportingproblems to the rest of the world and hegemony over other nations, isinconsistent with being a liberal, humane, and enlightened civilizatian thathas accepted democracy as philosophy of government, laissez-faire as itseconomic order, and rationalism and humanism as universal philosophy.It is our contention, however, that these varied philosophies do not standin contradiction to the imperialist epistemological vision. Rather, there isa close link between these philosophies and the imperialist vision, whichwill be fully undelstmd once we turn to the epistemological level. Inorder to be aware of such a link, it has to be recognized that all of thesephilosophies are secular in nature, in the sense that they do not admit ofany philosophical system outside the domain of the materialistic order.In our view, secularism is not a separation between religion and thestate, as propagated in both western and Arab writings. Rather, it is theremoval of absolute values-epistemological and ethical-from the worldsuch that the entire world-humanity and nature- alike-becomes merelya utilitarian object to be utilized and subjugated. From this standpoint, wecan see the structural similarity between the secular epistemologicalvision and the imperialist epistemological vision. We can also realize thatimperialism is no more than the exporting of a secular epistemologicaland ethical paradigm from the western world, where it first emerged, tothe rest of the world ...